The Composition of Fatty Acids in Ostrich Meat Influenced by the Type of Packaging and Refrigerated Storage - Olaf K. Horbańczuk; Małgorzata Moczkowska; Joanna Marchewka; Atanas G. Atanasov; Marcin A. Kurek (Molecules, 2019)
Ostrich meat is a high-quality dietetic product, however, it is very sensitive to deterioration during storage. The aim of this study was to assess the effect of packaging systems on the fatty acid (FA) profiles in ostrich meat during refrigerated storage. The systems were: Vacuum packaging (VP) and modified atmosphere packaging (MAP) in two combinations of gases: MAP1 (40% O2/40% CO2/20% N2) and MAP2 (60% O2/30% CO2/10% N2). Samples were taken from the M. ilifibularis (IF) muscles of eight ostriches in each treatment group. The packs were stored in a refrigerator at 2 °C and analyzed at 0, 4, 8, 12 and 16 days. The packaging conditions and storage time had an impact on the concentration of bioactive compounds such as polyunsaturated fatty acids (PUFA), including n-3 such as C18:3, C20:5 (EPA) and C22:6 (DHA). The least changes in composition of n-3 and the sum of PUFA were recorded in ostrich meat packaged in vacuum, followed by that packaged using MAP1 and MAP2. The sum of n-6 PUFAs decreased significantly by 2.1% for MAP2, and only by 0.7% for vacuum packaging as the experiment progressed. A significant deterioration of these compounds was observed in all package systems, especially from day 12 until day 16 of storage.